Profiling digital news portal based on manipulative writing using fuzzy logic - Che Eembi @ Jamil, Normala; Ishak, Iskandar; Sidi, Fatimah; Affendey, Lilly Suriani (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper carried a brief of overview of data veracity in model profiles of digital news portal. Veracity is a way to find the truthfulness, availability, accountability and authenticity. In this paper, the author will focus on data veracity to define truthfulness in a news article. People who read the news should know the aspects that make the news should be trustful or not. So the author proposes a model for profiling digital news portal particular in data veracity. There are various issues in manipulative writing that unable to determine the truthfulness. These issues will lead to the problem of manipulating from real news portal. Although there were many researchers doing the profiling on the web, most of the researcher focus on profiling social media user. The author wants to highlight that not only user’s profile contents but the news contents also is essential to manage the profile. So it is necessary to focus on profiling digital news portal to analyze its truthfulness including the news that they published. Based on the literature review the author found that there is a gap in profiling digital news portal in original manipulative writing from the truth that can give a critical problem in hiding information from original sources. The objective of this paper is to profile digital news portal based on manipulative writing using fuzzy logic.